Aktivitas Antibakteri Ekstrak Daun Kecapi (Sandoricum koetjape Merr.) - Pindo Hardika P.A.N; Aditya Fridayanti; Laode Rijai (Journal of Tropical Pharmacy and Chemistry, 2013)
A research has been conducted on the antibacterial activity of the santol leaves extract (S.koetjape Merr.) against S.aureus and E.coli. The santol leaves extracts were prepared by maceration used methanol as solvent and the methanol extract was then fractionated. The antibacterial activity was determined by measured the diameter of inhibition zones in difusi method. The result showed that santol leaves extracts and fractions has antibacterial activity against S.aureus and E.coli. The effective concentration as an antibacterial of methanol extracts is at 10%, and of n-hexane fractions is at 5%.